P13, the EMBL macromolecular crystallography beamline at the low‐emittance PETRA III ring for high‐ and low‐energy phasing with variable beam focusing. (9th December 2016) - Cianci, Michele; Bourenkov, Gleb; Pompidor, Guillaume; Karpics, Ivars; Kallio, Johanna; Bento, Isabel; Roessle, Manfred; Cipriani, Florent; Fiedler, Stefan; Schneider, Thomas R.
Abstract : The P13 macromolecular crystallography beamline, based on the low‐emittance source PETRA III, enables X‐ray diffraction experiments on macromolecular crystals over a wide wavelength range (0.7–3.1 Å). The beam has a variable focus size and a small divergence enabling data collection on micrometre‐sized crystals. Abstract : The macromolecular crystallography P13 beamline is part of the European Molecular Biology Laboratory Integrated Facility for Structural Biology at PETRA III (DESY, Hamburg, Germany) and has been in user operation since mid‐2013. P13 is tunable across the energy range from 4 to 17.5 keV to support crystallographic data acquisition exploiting a wide range of elemental absorption edges for experimental phase determination. An adaptive Kirkpatrick–Baez focusing system provides an X‐ray beam with a high photon flux and tunable focus size to adapt to diverse experimental situations. Data collections at energies as low as 4 keV (λ = 3.1 Å) are possible due to a beamline design minimizing background and maximizing photon flux particularly at low energy (up to 10 11  photons s −1 at 4 keV), a custom calibration of the PILATUS 6M‐F detector for use at low energies, and the availability of a helium path. At high energies, the high photon flux (5.4 × 10 11  photons s −1 at 17.5 keV) combined with a large area detector mounted on a 2gθ arm allows data collection to sub‐atomic resolution (0.55 Å). A peak flux of about 8.0 × 10 12  photons s −1 is reached at 11 keV. Automated sample mounting is available by means of the robotic sample changer `MARVIN' with a dewar capacity of 160 samples. In close proximity to the beamline, laboratories have been set up for sample preparation and characterization; a laboratory specifically equipped for on‐site heavy atom derivatization with a library of more than 150 compounds is available to beamline users.